Pembelajaran Berbasis Proyek Menggunakan Trainer Simulator AC Energi Hijau untuk Meningkatkan Kompetensi Guru SMK - Yunesman, Yunesman; Yasra, Refdilzon; Putri, Weni Lestari (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: This study was motivated by the low competence of vocational high school teachers in understanding and applying green energy concepts and learning technologies relevant to industrial needs. This condition highlights the need for training to improve teachers’ ability to meet workforce demands and align with the Indonesian Government’s Nawacita program to strengthen human resource quality. The purpose of this study was to determine the effectiveness of technology-based green energy training in improving teachers' competence at SMK Aljabar Batam. Method: The research employed a quantitative, one-group pretest–posttest design. Data were collected through pre- and post-tests, participant satisfaction questionnaires, and supporting interviews. Results: The results showed an average improvement in teacher competence of 30.2%, covering technical skills, understanding of green energy, pedagogical ability, and technology integration in learning. The participants’ satisfaction level was very good, with an average score of 4.66. Conclusion: The technology-based green energy training effectively improved vocational teachers’ competencies and can serve as a sustainable professional development model to enhance educational quality and national competitiveness.